362 Evaluation of Different Levels of Trace Mineral Supplementation to Calves Prior to Wearing. (21st September 2022) - Hernandez, Gracia M Puerto; Boyd, Derringer; Livingston, Julia; Gossbodily, Garrett; Bohnert, David; Ranches, Juliana
Abstract: A two-year study evaluated two different levels of trace mineral supplementation (Cu, Se, and Zn) to calves prior to weaning. Approximately 84 days prior to weaning, 24 calves/year (Angus × Hereford) were randomly assigned to one of two treatments: trace mineral supplementation following NASEM (2016) requirements (Control); and trace mineral supplementation above NASEM (2016) requirements (Super). Calves were individually fed and trace minerals were provided in 0.5 lb of dry distillers grains three times weekly. The total weekly amount of trace minerals was divided into three feeding events (Monday, Wednesday, and Friday). Body weight (BW), blood, and liver samples were collected on d 0 and at weaning (d 84). All data were analyzed using the MIXED procedure (SAS Inst. Inc., Cary, NC). No differences (P ≥ 0.69) were observed for the initial liver concentration of Se, Cu, and Zn. No differences (P = 0.54) were observed for liver Se concentration at weaning. A year effect (P < 0.0001) and a tendency for treatment x year effect (P = 0.09) were observed for liver Zn concentration at weaning. In year 1 but not in year 2, calves assigned to Control treatment had greater liver Zn concentration than calves assigned to Super treatment. For Cu liver concentration, a year effect (P < 0.0001) and a tendency for treatment x year effect (P = 0.09) were observed at weaning. In year 2, but not in year 1, calves assigned to Super treatment had greater liver Cu concentration than calves assigned to Control treatment. No treatment effects (P ≥ 0.23) were observed for BW or average daily gain pre- or post-weaning. Except for Cu, supplementation of trace minerals above the NASEM (2016) recommendations does not lead to improved mineral status of calves in this environment.